THE VARIATION OF LANGUAGE IN THE QUR'AN MINANG TRANSLATION; SOCIOLINGUISTICS REVIEW - Halim Andana (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
The main problem in this research is the discovery of the language variation in meaning or translate the word qa>la both in the same verse or different verse, the underlined is about the language variations with the focus of discussion in terms of the context and function of language. Through the method of descriptive-analytic, with overview of sociolinguistics, the results showed that the discovery of the factors that affect the variation of the selection language in the translate words qa>la specialized context; speakers, and partners said in events interaction, then the factors of the function of language; the intent and purpose of events interaction. In the Minang translation, the word qāla is translated with bakato in terms of language functions to request or request an explanation and terms of idiolects consists of various social status of the speaker and is used for speech partners with different social statuses. Then the word qa>la with manyabuik is used in the context of disaster/examination, and The word qāla is translated with bafirman in terms of language functions to provide important information. Finally, the presence of this article is expected to enrich the national interpretation in Indonesia.